2006
DOI: 10.1166/jnn.2006.125
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Biocompatibility of Carbon Nanoparticles

Abstract: A review is presented of the literature data concerning the effects induced by carbon nanoparticles on the biological environment and the importance of these effects in human and animal health. The discovery in 1985 of fullerenes, a novel carbon allotrope with a polygonal structure made up solely by 60 carbon atoms, and in 1991 of carbon nanotubes, thin carbon filaments (1-3 microm in length and 1-3 nm in diameter) with extraordinary mechanical properties, opened a wide field of activity in carbon research. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 25 publications
1
80
0
2
Order By: Relevance
“…Toxicological studies using a wide range of nanomaterials have been conflicting and inconclusive (1,2,(43)(44)(45)(46)(47)(48). Water solubility, dose, exposure time, and similar parameters all appear to influence the cytotoxicity of the fullerenes.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicological studies using a wide range of nanomaterials have been conflicting and inconclusive (1,2,(43)(44)(45)(46)(47)(48). Water solubility, dose, exposure time, and similar parameters all appear to influence the cytotoxicity of the fullerenes.…”
Section: Discussionmentioning
confidence: 99%
“…The possible applications for CNTs range from biomedicine to nanoelectronics and mechanical engineering. To improve the quality of life, nanotechnology has been used in consumer products ranging from health care to agriculture, and concerns about the possible side effects of this technology in ecosystems, human health, and agricultural industries has been addressed [1]. The global demand for CNTs is predicted to be more than many thousands of tons in a single year, and MWCNTs have already been appearing in the market in industrial quantities.…”
Section: Introductionmentioning
confidence: 99%
“…The results are consistent with the fact that dose is an important factor in the toxicity of carbon nanoparticles. 23,24 However, the toxic effects also depend on the type of cells, as it was observed that fibroblasts ( Figure 4) were less susceptible to HNC treatment than glioma cells. This might be explained by the high amount of HNC aggregates in fibroblast medium and lower affinity of the HNC particles to fibroblast cells, influencing adhesion to the cell membrane and probably HNC intake by cells.…”
Section: Discussionmentioning
confidence: 99%